Investigating the effect of ribavirin treatment on genetic mutations in Crimean–Congo haemorrhagic fever virus (CCHFV) through next‐generation sequencing. Issue 2 (17th February 2023) - D'Addiego, Jake; Elaldi, Nazif; Wand, Nadina; Osman, Karen; Bagci, Binnur Koksal; Kennedy, Emma; Pektas, Ayse Nur; Hart, Eilish; Slack, Gillian; Hewson, Roger
Abstract: Crimean–Congo haemorrhagic fever (CCHF) is the most widespread tick‐borne viral haemorrhagic fever affecting humans, and yet a licensed drug against the virus (CCHFV) is still not available. While several studies have suggested the efficacy of ribavirin against CCHFV, current literature remains inconclusive. In this study, we have utilised next‐generation sequencing to investigate the mutagenic effect of ribavirin on the CCHFV genome during clinical disease. Samples collected from CCHF patients receiving ribavirin treatment or supportive care only at Sivas Cumhuriyet University Hospital, Turkey, were analysed. By comparing the frequency of mutations in each group, we found little evidence of an overall mutagenic effect. This suggests that ribavirin, administered at the acute stages of CCHFV infection (at the World Health Organization‐recommended dose) is unable to induce lethal mutagenesis that would cause an extinction event in the CCHFV population and reduce viremia.